Synthetic features of new 1,2,4-triazole derivatives - Khilkovets, A. V.; Parchenko, V. V.; Хільковець, Анастасія Валеріївна; Парченко, Володимир Володимирович (My University, 2022)
The relevance of our study is due to the constant need to obtain new promising molecules that can have high pharmacological activity and low toxicity. That is why synthetic chemists around the world are actively searching for new methods for the synthesis of biologically active compounds and modifying already known molecules. Among heterocyclic systems, 1,2,4- triazole attracts our attention. It has been repeatedly proven that among the derivatives of 1,2,4- triazole, many interesting compounds have been found that have practical applications in medicine, pharmacy, veterinary medicine and in industry. So, in order to systematize and generalize the known data on new methods for obtaining derivatives of 1,2,4-triazole, we have analyzed many domestic and foreign literature sources.
Keywords: synthesis; physical and chemical properties; derivatives of 1,2,4-triazole